2022
DOI: 10.1002/anie.202213829
|View full text |Cite
|
Sign up to set email alerts
|

Access to N−CF3 Formamides by Reduction of N−CF3 Carbamoyl Fluorides

Abstract: The departure into unknown chemical space is essential for the discovery of new properties and function. We herein report the first synthetic access to N-trifluoromethylated formamides. The method involves the reduction of bench-stable NCF 3 carbamoyl fluorides and is characterized by operational simplicity and mildness, tolerating a broad range of functional groups as well as stereocenters. The newly made NÀ CF 3 formamide motif proved to be highly robust and compatible with diverse chemical transformations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…The authors demonstrated that nucleophilic defluorinative reactions of the carbamoyl fluorides can provide a diverse array of structurally complex N-trifluoromethyl amides, (thio)carbamates, ureas and formamides (Scheme 15, bottom). [80] These previously difficult-to-access structures are useful analogues of N-Me or N-H amides as the N-CF 3 derivatives can have improved stability towards basic and oxidative conditions.…”
Section: Defluorinative Synthesis Of N-trifluoromethylamide Derivativesmentioning
confidence: 99%
“…The authors demonstrated that nucleophilic defluorinative reactions of the carbamoyl fluorides can provide a diverse array of structurally complex N-trifluoromethyl amides, (thio)carbamates, ureas and formamides (Scheme 15, bottom). [80] These previously difficult-to-access structures are useful analogues of N-Me or N-H amides as the N-CF 3 derivatives can have improved stability towards basic and oxidative conditions.…”
Section: Defluorinative Synthesis Of N-trifluoromethylamide Derivativesmentioning
confidence: 99%
“…In the process, the Schoenebeck group developed a simple synthetic way to N-CF 3 formamides 8 from the N-CF 3 carbamoyl fluorides 2 for the first time. [7] The reduction was carried out with NaBH 4 in a mixture of dichloromethane and tert-Amyl alcohol ( t AmOH) at room temperature for 1 h. A large range of functional groups, such as aryls and aliphatics, could be tolerated in these mild conditions. The amino acid N-CF 3 formamides 8 n-q were also isolated without loss of their stereochemistry.…”
Section: Access To N-trifluoromethyl Formamidesmentioning
confidence: 99%
“…A nickel‐catalyzed coupling of N −CF 3 carbamoyl fluorides with alkynyl silanes yielded N −CF 3 alkynamides ( 11 ) (Scheme 1e), which were readily converted to the N −CF 3 decorated alkenyl amides, oxindoles, and quinolones [6f] . N ‐trifluoromethyl formamides ( 12 ) were also prepared by the reduction of bench‐stable N −CF 3 carbamoyl fluorides with NaBH 4 or NaBD 4 , tolerating a broad range of functional groups as well as stereocenters (Scheme 1f) [6g] . Thanks to these wide applications of carbamoyl fluorides, the development of efficient methods for the preparation of such compounds is highly sought after.…”
Section: Synthesis and Transformation Of Carbamoyl Fluorides And Thei...mentioning
confidence: 99%